G-Force Test Stand for the Evaluation of Weapon Component Strength - Damian GOŁOŚ; Michał JASIŃSKI; Paweł ZAWADA; Janusz NOGA (Problemy Mechatroniki)
This paper discusses the design of a G-force test stand intended to examine of the effects of mechanical loads present during firing of a weapon and applied to the electronic components contained in the 155 mm calibre guided projectile. The G-force test stand is used to develop and test the effects of using high mechanical loads by decelerating a test specimen through the use of a purpose-designed fender assembly. For the purpose of testing, it is irrelevant whether a load is developed by acceleration or deceleration of the test specimen, as a test result obtained by the deceleration of a test specimen is equivalent to a test result obtained by the acceleration of a test specimen, as used in a 155 mm calibre artillery guided projectile. The G-force test stand was used to test and determine the velocities developed by the test specimens and the G-forces applied to them. The maximum velocity to which a test specimen was accelerated was approx. 72 m/s. The test stand was able to propel the test specimens to velocities an order of magnitude higher than the velocities obtained with a Kast and Masset ram. The tests were performed with rubber and copper fender assemblies. The effect of the specific fender used was demonstrated on the trend of the generated G-force. The test stand could develop G-forces in excess of 10,000 with a duration of more than 500 µs.